2018
DOI: 10.1002/mma.5198
|View full text |Cite
|
Sign up to set email alerts
|

Threshold behavior in a stochastic HTLV‐I infection model with CTL immune response and regime switching

Abstract: We investigate the stochastic HTLV-I infection model with CTL immune response, which is disturbed by both white and telegraph noises. First, we obtain that the model solution is positive and global. Furthermore, we obtain the existence of ergodic stationary distribution of the solution by stochastic Lyapunov functions with regime switching, and we also establish sufficient conditions for the extinction of system with regime switching. Meanwhile, the threshold R * 0 between ergodic property and extinction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Proof. Using the same method as [17], when the local solution of the system (2) is global with the initial value…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Using the same method as [17], when the local solution of the system (2) is global with the initial value…”
Section: Theoremmentioning
confidence: 99%
“…Actually, in the real world, environmental noise is an inevitable important factor, so the epidemic model will be affected by environmental noise [13][14][15][16][17][18][19][20]. In this paper, we will consider a type of environmental noise (namely white noise) with the system (1).…”
Section: Introductionmentioning
confidence: 99%
“…23 Therefore, the existence of stationary distribution has attracted lots of researchers' attention in the recent years. 1,11,20,[24][25][26][27][28] As we can see, to prove the existence of stationary distribution, it is usually the discussion about the nonpositiveness of the Khasminskii-Lyapunov function that is outside of the sufficiently large closed set with the action diffusion operator, which is like to literatures. 11,20,24 Some recent studies [26][27][28] have shown that we can discuss the existence of stationary distribution based on a bounded set when the solution of stochastic system is bounded.…”
Section: 𝑦(T) = 𝛽X(t)𝑦(t) − 𝛾𝑦(T)z(t) − 𝜇 2 𝑦(T)mentioning
confidence: 99%
“…CTLs (Cytotoxic T Lymphocytes) play a significant role in antiviral mechanisms. On the one hand, CTLs imply the main immune factor inhibiting cell that limits the development of virus replication in vivo and depends on viral load [ 11 , 12 , 13 ]; on the other hand, it has recently been demonstrated that infected cells are killed not by the virus but by specific CTLs in some infectious diseases such as hepatitis B [ 3 , 14 ]. Therefore, the dynamics of the epidemic viral model with CTL responsiveness have drawn much attention from researchers in related areas [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%